2000
DOI: 10.1177/0265407500173002
|View full text |Cite
|
Sign up to set email alerts
|

'I Like you... as a Friend': The Role of Attraction in Cross-Sex Friendship

Abstract: This study investigated attraction in heterosexual cross-sex friendships. Study I used in-depth interviews with 20 dyads (40 participants) to uncover four types of attraction that occur in cross-sex friendships - subjective physical/sexual attraction, objective physical/sexual attraction, romantic attraction, and friendship attraction. These types of attraction are subject to being symmetrical or asymmetrical, and may incur changes over time. Study 11 (N = 231) used a questionnaire to assess the frequency of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 23 publications
2
37
0
6
Order By: Relevance
“…Research has found that a considerable percentage of university students have engaged in sexual activity with a friend, and prevalence rates have ranged from 49 to 62% (Afifi & Faulkner, 2000;Mongeau et al, 2003;Reeder, 2000). The current study sought to replicate these findings regarding the prevalence of FWB among college students.…”
Section: Preliminary Definitionsmentioning
confidence: 77%
“…Research has found that a considerable percentage of university students have engaged in sexual activity with a friend, and prevalence rates have ranged from 49 to 62% (Afifi & Faulkner, 2000;Mongeau et al, 2003;Reeder, 2000). The current study sought to replicate these findings regarding the prevalence of FWB among college students.…”
Section: Preliminary Definitionsmentioning
confidence: 77%
“…Sexual attraction to friends is, however, more prominent at the onset of the relationship for women and reduces with time (Reeder, 2000). Our friend narratives described a sexual interaction with a close, long-term friend and may, therefore, have been less sexually-arousing to women.…”
Section: Relationship Contextmentioning
confidence: 85%
“…To assess physical attraction, we created four items based on Reeder's (2000) four types of attraction in cross-sex friendship ("I feel close and connected to this person as a friend, but nothing more," "I think my friend is attractive in general, but I don't feel the attraction myself," "My friend is not sexually attractive to me," all reverse coded, and "I feel physically attracted to my friend"). Participants rated their agreement with each statement on a five point scale (5 = strongly agree; 1 = strongly disagree) and we averaged across items to compute the scale,  = .84.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%